Diseño de un producto turístico para la parroquia Timbara del cantón Zamora, provincia Zamora Chinchipe. - Ordoñez Montaño, Janeth Maribel (2022)
This research allows obtaining data on the current situation for the strengthening and development of the Timbara parish, taking into account that there is not enough supply of services in the sector, the lack of tourism infrastructure, the low tourism promotion by the parish government. Due to its characteristics, this parish has a great tourist potential that allows the development of tourist activities in a planned and organized way, by proposing tourist products aimed at diversifying the offer, thus the proposal of the Ruta de la Caña y la Melcocha, which through surveys and interviews was able to obtain the necessary information on the requirements of the SWOT analysis, thus resulting in two market segments such as: students and professionals. For the research work, a general objective was formulated: "To design a tourism product for the development of the Timbara parish in the Zamora canton, Zamora Chinchipe province"; three specific objectives were also formulated: "Determine the current tourism situation of Timbara parish of Zamora canton of Zamora Chinchipe province", "Make a proposal for tourism products in Timbara parish of Zamora canton, Zamora Chinchipe province", "Establish a promotion and marketing plan for tourism products for Timbara parish of Zamora canton of Zamora province of Zamora Chinchipe". In the methodology for the first objective, which determines the current tourism situation of the Timbara parish, the Carla Ricaurte matrix was used for the current local tourism diagnosis, as well as the application of techniques such as surveys, interviews and direct observation, and at the same time using the tourism inventory cards of the Ministry of Tourism (MINTUR), through which the main tourist attractions of the parish were collected, thus having current information for the development of the SWOT matrix, whose results establish strategies to design the proposal of tourism products. For the second objective, through the strategies of the SWOT analysis, the tourist products were determined, following the methodology described in the Manual for the generation of tourist routes and itineraries of the MINTUR 2017 and for the elaboration of the signage, the Manual of tourist signage of the MINTUR was applied. For the third objective where a plan for the promotion and marketing of tourism products for the Timbara parish is established, surveys were used, which were applied at strategic points in the provinces of Loja and Zamora resulting in the use of tools such as social networks, blog on the website of the parish GAD, thematic clothing, tourist fair, brochures, souvenirs, advertising spot, billboard, as part of the proposed strategy.